CONSUMER PROTECTION UNDER ISLAMIC LAW IN E COMMERCE TRANSACTIONS: A CASE STUDY OF SHOPEE USERS IN PIDIE DISTRICT, INDONESIA - M. Darul Kamal; Saifuddin Sadan; Chairul Baria (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This paper examines consumer protection in online buying and selling transactions via Shopee according to Islamic law (a case study in Sigli City). It employs qualitative research methods and a normative juridical approach. Data was obtained through interviews and direct review of the accounts @mawaddah and @warahmah. The results indicate that errors were made by the seller, as well as a lack of response from the seller to complaints from buyers, and the seller is not held responsible for these errors. According to Islamic law, all types of transactions are permissible, provided they adhere to and comply with applicable Islamic law. All buying and selling activities must meet the relevant requirements and legal provisions. Once these conditions are met, the rights and obligations of both parties apply.